2008
DOI: 10.1007/s10796-008-9070-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the outsourcing learning curve: A longitudinal analysis of a large Australian company

Abstract: Outsourcing continues to capture the attention of researchers as more companies move to outsourcing models as part of their business practice. Two areas frequently researched and reported in the literature are the reasons why a company decides to outsource, and outsourcing success factors. This paper describes an in-depth, longitudinal case study that explores both the reasons why the company decided to outsource and factors that impact on success. The paper describes how Alpha, a very large Australian communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 23 publications
0
42
1
3
Order By: Relevance
“…• Domestic outsourcing is often sought for many reasons, including cost reduction, access to new or specialized expertise, and facilitating the firm's focus on core competencies (Lacity and Hirschheim,1993a,b;1995;Fisher et al, 2008).…”
Section: Sourcing Mode Triangular Alignment Hypothesismentioning
confidence: 99%
“…• Domestic outsourcing is often sought for many reasons, including cost reduction, access to new or specialized expertise, and facilitating the firm's focus on core competencies (Lacity and Hirschheim,1993a,b;1995;Fisher et al, 2008).…”
Section: Sourcing Mode Triangular Alignment Hypothesismentioning
confidence: 99%
“…Thus, selective outsourcing is much more recommended than total outsourcing. Aligned, with the previous argument, a case study by Fisher et al [4] on Alpha's (a large Australian telecommunication company) ITO practice also indicated that selective outsourcing could produce a better outcome compared to total outsourcing. During the first outsourcing wave, Alpha decided to outsource all of their IT functions and two third of their applications and business functionality.…”
Section: Selective Outsourcingmentioning
confidence: 68%
“…The client organizations are suggested to retain their core capabilities in-house and only consider outsourcing their non-core capabilities [4,11]. However, identifying the organization's core capabilities is easier said than done, thus Willcocks & Lacity [11] propose a framework which could be used to identify the client QoR VS Client's satisfaction [7] core capabilities.…”
Section: Client Core Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 121 articles resulted from the initial search. However, some of them were finally not considered, namely: an article that was a teaching case (Ranganathan, Krishnan and Glickman 2007), six editorials in various journals, eighteen articles which could not be classified as research works because they were opinion columns -all of them published in the journals CACM and ISM-and seven works which, despite dealing with outsourcing or internationalization, did not really fit into the area of offshore outsourcing (such as Fisher, Hirschheim and Jacobs (2008) or Rouse and Baba (2006)). This left us with 89 articles apt for the analysis which went through a complete and exhaustive reading.…”
Section: Methodology and Data Collectionmentioning
confidence: 99%